2014
DOI: 10.1073/pnas.1402152111
|View full text |Cite
|
Sign up to set email alerts
|

Tip-link protein protocadherin 15 interacts with transmembrane channel-like proteins TMC1 and TMC2

Abstract: The tip link protein protocadherin 15 (PCDH15) is a central component of the mechanotransduction complex in auditory and vestibular hair cells. PCDH15 is hypothesized to relay external forces to the mechanically gated channel located near its cytoplasmic C terminus. How PCDH15 is coupled to the transduction machinery is not clear. Using a membrane-based two-hybrid screen to identify proteins that bind to PCDH15, we detected an interaction between zebrafish Pcdh15a and an N-terminal fragment of transmembrane ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
179
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 31 publications
(42 reference statements)
4
179
0
Order By: Relevance
“…[27][28][29][30][31][32][33] PCDH15 forms the lower portion of the tip-link and is believed to interact with a mechanotransduction channel that allows hair cells to respond to physical forces. 34,35 Consistent with studies on the IMAC, formation of the tip-link complex also appears to be critical for hair bundle organization. 36 Thus, a conserved apical adhesion complex consisting of 2 cadherin family members, 2 scaffolding proteins, and a myosin motor, physically connects and organizes protrusions in apical specializations with entirely distinct morphologies and physiological functions ( Table 1, Fig.…”
Section: Parallels Between Imacs and Stereocilia Tip-links -Implicatisupporting
confidence: 65%
“…[27][28][29][30][31][32][33] PCDH15 forms the lower portion of the tip-link and is believed to interact with a mechanotransduction channel that allows hair cells to respond to physical forces. 34,35 Consistent with studies on the IMAC, formation of the tip-link complex also appears to be critical for hair bundle organization. 36 Thus, a conserved apical adhesion complex consisting of 2 cadherin family members, 2 scaffolding proteins, and a myosin motor, physically connects and organizes protrusions in apical specializations with entirely distinct morphologies and physiological functions ( Table 1, Fig.…”
Section: Parallels Between Imacs and Stereocilia Tip-links -Implicatisupporting
confidence: 65%
“…Because PCDH15 forms the lower portion of the tip link where the mechanotransduction channels are located (Beurg et al, 2009), it is well positioned to interact with other components of the mechanotransduction complex. Indeed, the transmembrane and cytoplasmic domains of PCDH15 have been shown to interact with transmembrane channel-like (TMC) proteins (Maeda et al, 2014), Lipoma HMGIC fusion partner-like 5 (LHFPL5) , and, in the case of PCDH15-CD2, with transmembrane inner ear (TMIE) . Although these interactions are of particular interest when considering how the tip link is tethered to other components of the mechanotransduction complex, it is not clear what domains of PCDH15 are essential for mechanotransduction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that there are only two isoforms of Pcdh15a in zebrafish, Pcdh15a-CD1 and Pcdh15a-CD3. The Pcdh15a-CD2 isoform is not detectable at either the transcript level nor within the genomic region of pcdh15a (Seiler et al, 2005;Maeda et al, 2014). As in mammals, the zebrafish CD1 and CD3 isoforms share the extracellular cadherin repeats, the transmembrane domain, and the intracellular common region.…”
Section: Introductionmentioning
confidence: 99%
“…How these proteins get to the top of the bundle and connect up with a linkage, the "tip link," necessary to make a fast response to any sound disturbance, remains unresolved. The hair bundle itself is an organelle with over 200 proteins (4) and, although other components of the transduction complex are known (5,6), their organization remains a puzzle. To open the channel, the bundle needs to be deflected toward the tallest hairs.…”
mentioning
confidence: 99%